Application in Basic Marketing: Clippings from the Popular Business Press - William D. Perreault, E. Jerome McCarthy (McGraw Hill, 2005)
This book provide a flexible and helpful set of teaching and learning materials, include clipping (articles) on a wide variety of topics. the clippings deal with consumer products and bisiness products, good and services, new developments in marketing as well as traditional issues, and large well-know companies as well as new, small ones.